1987
DOI: 10.1093/genetics/116.1.153
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Neutral Molecular Evolution Based on Nucleotide Data

Abstract: The neutral theory of molecular evolution predicts that regions of the genome that evolve at high rates, as revealed by interspecific DNA sequence comparisons, will also exhibit high levels of polymorphism within species. We present here a conservative statistical test of this prediction based on a constant-rate neutral model. The test requires data from an interspecific comparison of at least two regions of the genome and data on levels of intraspecific polymorphism in the same regions from at least one speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
207
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,556 publications
(215 citation statements)
references
References 15 publications
5
207
0
3
Order By: Relevance
“…Figure 6 further suggests that the distribution of variants in the hypervariable region is incompatible with a neutral explanation. Only one previous study, that of Kreitman and others on Drosophila melanogaster Adh, has identified a similar peak of polymorphism (KREITMAN and AGUADE 1986;HUDSON et al 1987;KREITMAN and HUDSON 1991). As this peak flanks the amino acid polymorphism causing the electrophoretic difference between D. melanogaster Adh alleles, these authors have concluded that the amino acid polymorphism is subject to balancing selection.…”
Section: Variation In Intensities Of Purifying Selectionmentioning
confidence: 90%
See 3 more Smart Citations
“…Figure 6 further suggests that the distribution of variants in the hypervariable region is incompatible with a neutral explanation. Only one previous study, that of Kreitman and others on Drosophila melanogaster Adh, has identified a similar peak of polymorphism (KREITMAN and AGUADE 1986;HUDSON et al 1987;KREITMAN and HUDSON 1991). As this peak flanks the amino acid polymorphism causing the electrophoretic difference between D. melanogaster Adh alleles, these authors have concluded that the amino acid polymorphism is subject to balancing selection.…”
Section: Variation In Intensities Of Purifying Selectionmentioning
confidence: 90%
“…For this reason we have sequenced the same region from a number of closely related species. This also provides both phylogenetic information and an interspecific comparison for future tests of selective neutrality (i.e., HUDSON et al 1987). Our sequence analysis of species related to A. thaliana includes C. arenosa, H. diffusa, C. bursa-pastoris, A .…”
Section: Figure 1-(a)mentioning
confidence: 99%
See 2 more Smart Citations
“…2020). For example, presence of balancing (i.e., diversifying) selection at the Adh locus in Drosophila was discovered by an excess of nucleotide polymorphisms in the coding region relative to the 5’-flanking sequences (HKA test) (Hudson et al . 1987).…”
Section: Introductionmentioning
confidence: 99%